Can Knowledge Sharing and Work Proffesionalism Create a Conducive Organizational Climate? - Jubery Marwan; Zahera Mega Utama (IJHCM (International Journal of Human Capital Management), 2024)
AbstractThe role of human resources in creating a good organizational climate is an issue that has been researched previously. However, if we look at the effectiveness criteria presented by experts in the field of management, we understand that knowledge-sharing behavior and work professionalism can directly or indirectly play a very important role in improving employee performance. This study aims to analyze the contribution of knowledge sharing and work professionalism to creating a good organizational climate through emotional intelligence. This research was conducted at University of Prof. Dr. Moestopo (Beragama), Jakarta. Researchers use questionnaires as a tool to obtain primary data. Sampling used the entire population of 168 respondents. The research results show that: 1) knowledge sharing and work professionalism contribute significantly to emotional intelligence; 2) knowledge sharing and work professionalism contribute significantly to emotional intelligence, both directly and indirectly, to the organizational climate through emotional intelligence. Knowledge sharing and work professionalism behavior in an organization can create several positive things, including good organizational decision-making, a good organizational climate, and increased knowledge distribution on a more complex team work scale. The ability to manage emotional intelligence can create a good organizational climate. However, managing each individual's emotional intelligence depends on how much the individual is able to respond to their own emotional strength.